Fibrin-Targeted Nanoparticles for Finding, Visualizing and Characterizing Blood Clots in Acute Ischemic Stroke - María Luz Alonso-Alonso; María Pérez-Mato; Ana Sampedro-Viana; Clara Correa-Paz; Paulo Ávila-Gómez; Tomás Sobrino; Francisco Campos; José Castillo; Ramón Iglesias-Rey; Pablo Hervella (MDPI AG, 2022)
Recanalization of the occluded artery is the gold standard treatment for acute ischemic stroke, which includes enzymatic fibrinolytic treatment with the use of recombinant tissue plasminogen activators (rtPAs) to disrupt the occluding clot, the use of mechanical thrombectomy to physically remove the clot, or a combination of both. Fibrin is one of the main components of blood clots causing ischemic stroke and is the target of rtPA upon activation of plasminogen in the clot. In addition, fibrin content also influences the efficacy of mechanical thrombectomy. Current imaging methods can successfully identify occlusions in large vessels; however, there is still a need for contrast agents capable of visualizing small thrombi in ischemic stroke patients. In this work, we describe the synthesis and the in vitro characterization of a new diagnostic nanoparticle, as well as the in vivo evaluation in an animal model of thromboembolic stroke. Gd-labeled KCREKA peptides were synthesized and attached onto the surface of PEGylated superparamagnetic nanoparticles. Magnetic resonance imaging (MRI) of blood clots was performed in vitro and in vivo in animal models of thromboembolic stroke. KCREKA-NPs were synthesized by attaching the peptide to the amino (N) termini of the PEG-NPs. The sizes of the nanoparticles, measured via DLS, were similar for both KCREKA-NPs and PEG-NPs (23 ± 4 nm, PDI = 0.11 and 25 ± 8 nm, PDI = 0.24, respectively). In the same line, r2 relaxivities were also similar for the nanoparticles (149 ± 2 mM Fe s−1 and 151 ± 5 mM Fe s−1), whereas the r1 relaxivity was higher for KCREKA-NPs (1.68 ± 0.29 mM Fe s−1 vs. 0.69 ± 0.3 mM Fe s−1). In vitro studies showed that blood clots with low coagulation times were disrupted by rtPA, whereas aged clots were almost insensitive to the presence of rtPA. MRI in vitro studies showed a sharp decrease in the T1 × T2 signals measured for aged clots incubated with KCREKA-NPs compared with fresh clots (47% [22, 80] to 26% [15, 51]). Furthermore, the control blood showed a higher value of the T1 × T2 signal (39% [20, 61]), being the blood clots with low coagulation times the samples with the lowest values measured by MRI. In vivo studies showed a significant T1 × T2 signal loss in the clot region of 24% after i.v. injection of KCREKA-NPs. The thrombus age (2.5% ± 6.1% vs. 81.3% ± 19.8%, p < 0.01) confirmed our ability to identify in vivo fresh blood clots. In this study, we developed and tested a dual MRI nanoparticle, acting as T1 and T2 contrast agents in MRI analyses. The developed KCREKA-NPs showed affinity for the fibrin content of blood clots, and the MRI signals provided by the nanoparticles showed significant differences depending on the clot age. The developed KCREKA-NPs could be used as a tool to predict the efficacy of a recanalization treatment and improve the triage of ischemic stroke patients.